Study of Effectiveness of Selected Investment Funds with Assets in the Polish Real Estate Market - Tomal, Mateusz (Journal of Finance and Financial Law, 2017)
The examination of the effectiveness of investment funds is a frequently observed phenomenon. However, such analyses largely concern stock and bond funds. It appears that due to their relatively young age as products on the Polish financial market and the radically different objective of investment real estate funds should be subject to extensive research. The aim of the presented study was to investigate the effectiveness of selected investment funds with assets in the Polish real estate market in 2014–2016. Throughout the course of empirical research four selected investment funds were examined using relative and absolute measurements of effectiveness. Analysis of data showed that the majority of investment funds operating on the real estate market actually achieved poor results. This may be due to a lack of prior knowledge and expertise of manager presiding over the fund, but also due to bad investment policies.